Language promotion in everyday interactions within play groups: What kind of interactions occur between playgroup leaders and children? - Kannengieser, Simone; Tovote, Katrin (Swiss Journal of Educational Research, 2018)
Playgroups are considered suitable social settings for early childhood second language support. The corresponding in-service training program for playgroup leaders of the Canton of Basel-Stadt emphasizes the method of daily activity-based language support. According to this approach, all everyday conversations –initiated by both the adult and the child – can serve as language promotion opportunities. In the sub-study of the SNF research project “MeKi – Early language support of multilingual preschool children above age 3“, interactions between playgroup leaders and individual target children are video-taped and analyzed using linguistic conversation analysis. The current article focuses on the empirically identified types of interactions, and the interpretation of their value for language promotion.